The Important Roles of BIM in the Construction Industry in Vietnam: A Multi-approach Analysis - Pham, Van Duong; Ta, Van Phan; Nguyen, Minh Ngoc; Nguyen, Van Viet; Mai, Vu (International Journal of Sustainable Construction Engineering and Technology, 2024)
Building Information Modeling (BIM) is a good approach to solving problems in the construction projects, it plays an important role in developing strategy of the Vietnamese construction industry. This study aims to comprehensively analyze the role of BIM by collecting data and evaluating its impact on the industry. Specifically, this study examines legal documents related to BIM across different periods, surveys 150 construction jobs and 74 bidding documents to assess the demand for BIM process, and evaluates the practical benefits of BIM for construction projects. In addition, this study analyzed and clarified the effectiveness of applying BIM to construction projects compared to 2D technology. The findings elucidate BIM’s roles in driving industry shifts, including alignment with new policies, trends in human resource training, and enhanced transparency in project management. Finally, this study provides insights into Vietnam’s roadmap for BIM adoption in the construction sector through 2030 and beyond.